Obligations Arising from Public International Law Relating to the Rights of Minorities - Some Obervations on the Case of Kosovo - Tóth, Norbert; Vizi, Balázs (Pécs journal of international and European law, 2023)
This article intends to highlight certain questions relevant to the understanding of the current international legal situation of Kosovo particularly in fields of ensuring human and minority rights and international treaty obligations relating thereto. Additionally some pieces of Kosovo’s domestic legislation on minority issues shall also be reviewed. This article’s main question is how a State with limited recognition and restricted capacity to accede international treaties shall manage obligations arising primarily from treaties for stabilizing and improving her status within the international community.